Properties of the organic fraction directed to biostabilization in MBT installations during the heating season = Właściwości frakcji organicznej kierowanej do biostabilizacji w instalacjach MBP w okresie zimowym - Jędrczak, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the professional literature, there is no information about the sieve and morphological composition OFMSW (<80 mm) subjected to biological processing in MBT installations during the heating season. Knowledge about the quality of this fraction is important because it significantly affects the course of the biostabilization process.
Keywords: municipal solid waste; MBT plants; OFMSW; composting system; organic fraction; biodegradable waste; odpady komunalne; instalacja MBP; biofrakcja; systemy kompostowania; frakcja organiczna; odpady ulegające biodegradacji